2021
DOI: 10.1002/ajb2.1764
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of single visit pollination effectiveness comparing honeybees and other floral visitors

Abstract: Premise Many animals provide ecosystem services in the form of pollination including honeybees, which have become globally dominant floral visitors. A rich literature documents considerable variation in single visit pollination effectiveness, but this literature has yet to be extensively synthesized to address whether honeybees are effective pollinators. Methods We conducted a hierarchical meta‐analysis of 168 studies and extracted 1564 single visit effectiveness (SVE) measures for 240 plant species. We paired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…For example, the generally positive direct effect of honey bee visits may be of greater importance in the absence of competition; in cases where native pollinators have become rare or locally extinct, honey bees often increase pollination (Hanna et al, 2013; Lomov et al, 2010) and can even “rescue” plant populations from reproductive failure in isolated habitat fragments (Dick, 2001). However, negative indirect effects may occur and even outweigh direct effects when honey bees competitively displace native pollinators, especially when honey bees are ineffective substitutes (Page et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the generally positive direct effect of honey bee visits may be of greater importance in the absence of competition; in cases where native pollinators have become rare or locally extinct, honey bees often increase pollination (Hanna et al, 2013; Lomov et al, 2010) and can even “rescue” plant populations from reproductive failure in isolated habitat fragments (Dick, 2001). However, negative indirect effects may occur and even outweigh direct effects when honey bees competitively displace native pollinators, especially when honey bees are ineffective substitutes (Page et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta‐analyses showed that honeybees are generally less efficient when compared to the most efficient non‐ Apis pollinators for various plant species (Hung et al, 2018; Page et al, 2021), and this is particularly true for when honeybees are compared to birds (Page et al, 2021). It also applies both where honeybees are native (e.g., Brown et al, 2009) and where they are introduced (e.g., Celebrezze and Paton, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The western honeybee, Apis mellifera L., is native to Europe, Africa, and the Middle East, but due to beekeeping it is now distributed around the world (Han et al, 2012). Honeybees are also the most widely used and economically valuable pollinator of crops in monoculture worldwide (Klein et al, 2007), but there is increasing evidence that they are not particularly effective pollinators in either agricultural or in natural environments (Garibaldi et al, 2014; Hung et al, 2018; Page et al, 2021). Just over 50 years ago, Free (1966a) published an important, but often overlooked, paper that used mark‐recapture data to show that honeybees tend to confine their activities to single apple trees, even during subsequent foraging bouts.…”
mentioning
confidence: 99%
“…Previous studies showed that ecosystem service delivery is positively influenced by the richness of serviceproviding organisms like flower visitors (Dainese et al 2019). Although honeybees (mainly the European honeybee Apis mellifera L.) are kept worldwide to provide crop pollination, other insects (such as wild bees, flies, beetles, wasps) contribute a lot more to total pollination than previously thought (Rader et al 2016;Page et al 2021). Floral abundance and richness are important for crop pollination services from unmanaged flower visitors (Kremen et al 2007;Garibaldi et al 2014), thus wild pollinator communities should be supported by increasing the floral abundance and richness in their environment.…”
Section: Discussionmentioning
confidence: 99%